Tongan metaphors of social work practice : Hangē ha pā kuo fa'u´ : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Social Work at Massey University, Palmerston North, New Zealand - Mafileʻo, Tracie Ailong (Massey University, 2005)
This study explores Tongan social work practice and examines how social and community work is constructed from a Tongan worldview. Tongan social workers in Aotearoa New Zealand participated in individual interviews and focus group meetings which explored the Tongan values, knowledge, skills and processes foundational to their practice. The participants' narratives contribute to an understanding of Tongan conceptions of wellbeing, personal and social change and to an identification of key components of a Tongan theoretical framework for social and community work practice. This exploratory study contributes to the growing literature articulating indigenous and non-western frameworks for social and community work practice. Seeking to draw on a Tongan interpretive framework, the thesis employs metaphors, in particular two fishing practices (pola and uku), to draw the findings together. Pola, a community fishing practice, illustrates a Tongan social welfare system comprised of core values, namely: fetokoni'aki (mutual helpfulness), tauhi vā (looking after relationships), faka'apa'apa (respect) and 'ofa (love). Maintaining this Tongan system in the diaspora is central to the purpose of Tongan social and community work and the values themselves are a basis for practice. Other key concepts are shown to define a Tongan practice framework and these are identified as: fakafekau'aki (connecting), a'u tonu (going in person), lotu (spirituality/prayer/religion), fakatōkilalo (humility), fie'aonga (wanting to be useful), matakāinga (behaving like family) and 'osikiavelenga (doing utmost). The uku metaphor draws parallels to specialised practices of fishing or diving under the reef, around pupu'a puhi (blowholes). Similarly, Tongan social and community work involves specific processes which draw on a constellation of skills and values. Fakatoukatea (skills in opposite directions) is important for bridging Tongan and pālangi contexts, for working across various fields of practice and for adopting family-like roles as a social worker. Lea fakatonga (Tongan language), hua (humour)and feongo'i'aki (intuitive use of feelings) are important aspects of a Tongan social work approach. Tongan social and community work is located primarily within kāinga (extended family) and community. This location of social work reconstructs conventional conceptions of professionalism and relationships become a key force for change within a Tongan framework. A balance between a directive and empowerment approach needs to be achieved and an advocacy emphasis is required given the position of Tongans in the diaspora. This thesis demonstrates that a framework for social and community work derived from a Tongan worldview: provides new discourses and thinking within the critical postmodern tradition; is negotiated alongside other discourses thus creating spaces of possibility; is characterised by layers of ethnic specific, indigenous and humanity level differences and commonalities; emphasises the moral-artistic nature of social and community work; and challenges social work to be more diverse in terms of practice competencies, supervision, cross-cultural practice, education and community development. The thesis argues that if social and community work is to be transformative, it must itself be transformed and its very foundations reshaped by Tongan and other indigenous, non-western voices.
Keywords: Tongan community; Social work practice; Fields of Research::370000 Studies in Human Society::370200 Social Work